2015
DOI: 10.1037/spq0000056
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-efficacy mediates the effects of school psychological climate on academic achievement.

Abstract: This study investigated the effects of proximal and distal constructs on adolescent's academic achievement through self-efficacy. Participants included 482 ninth- and tenth- grade Norwegian students who completed a questionnaire designed to assess school-goal orientations, organizational citizenship behavior, academic self-efficacy, and academic achievement. The results of a bootstrapping technique used to analyze relationships between the constructs indicated that school-goal orientations and organizational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 51 publications
3
61
1
15
Order By: Relevance
“…The results of this study showed that academic hardiness may explain why students with a high sense of school belonging are more likely to show lower levels of academic stress. The mediation analysis indicated that greater levels of academic hardiness observed in students with a significant sense of belonging to school explained their lower levels of academic stress, which indicates that academic hardiness plays a key role in understanding the school belonging academic stress relationship (Abdollahi & Noltemeyer, 2018; Høigaard et al, 2015). A sense of school belonging has been found to have a significant and positive association with academic motivation, self‐regulation, and positive attitudes toward learning (Abdollahi & Noltemeyer, 2018; Allen et al, 2018; Hystad et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that academic hardiness may explain why students with a high sense of school belonging are more likely to show lower levels of academic stress. The mediation analysis indicated that greater levels of academic hardiness observed in students with a significant sense of belonging to school explained their lower levels of academic stress, which indicates that academic hardiness plays a key role in understanding the school belonging academic stress relationship (Abdollahi & Noltemeyer, 2018; Høigaard et al, 2015). A sense of school belonging has been found to have a significant and positive association with academic motivation, self‐regulation, and positive attitudes toward learning (Abdollahi & Noltemeyer, 2018; Allen et al, 2018; Hystad et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that TKD training resulted in a significantly high Self-confidence score (which indicates students’ confidence or conviction in their own academic capability). According to preceding research, there is a direct and indirect correlation between academic self-efficacy and academic achievement, as the learners with higher academic self-efficacy tend to choose more challenging tasks, invest more efforts in successfully carrying out tasks, and use more effective learning strategies9, 14, 15 ) . Taken together, these results suggest that TKD training may also be effective for enhancing academic capability in growing children.…”
Section: Discussionmentioning
confidence: 99%
“…Academic self-efficacy has been found to predict academic achievement, high school rank, and performance on standardized academic tests, [19][20][21][22] to influence career decision making, 23 and to promote academic persistence and high academic aspirations. 22,24 In addition, academic self-efficacy had the strongest relationship with academic achievement in a meta-analysis examining motivational constructs.…”
Section: Academic Self-efficacymentioning
confidence: 99%